2008
DOI: 10.1021/es702196a
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Abiotic Anaerobic Transformations of Trichloroethene and cis-1,2-Dichloroethene in Fractured Sandstone

Abstract: A fractured sandstone aquifer at an industrial site in southern California is contaminated with trichloroethene (TCE) and cis-1,2-dichloroethene (cis-DCE) to depths in excess of 244 m. Field monitoring data suggest that TCE is undergoing reduction to cis-DCE and that additional attenuation is occurring. However, vinyl chloride (VC) and ethene have not been detected in significant amounts, so that if transformation is occurring, a process other than reductive dechlorination must be responsible. The objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 18 publications
3
34
0
3
Order By: Relevance
“…Their roles have been demonstrated in several earlier studies of natural geochemical conditions (Davis et al, 2003;Lookman et al, 2005;Darlington et al, 2008). These studies also show that in addition to TCE, FeS is reactive toward a range of organic contaminants that are commonly observed in groundwater at hazardous waste sites.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Their roles have been demonstrated in several earlier studies of natural geochemical conditions (Davis et al, 2003;Lookman et al, 2005;Darlington et al, 2008). These studies also show that in addition to TCE, FeS is reactive toward a range of organic contaminants that are commonly observed in groundwater at hazardous waste sites.…”
Section: Discussionsupporting
confidence: 60%
“…Among these, iron sulfide minerals have been shown to be the most potent minerals for abiotic dechlorination (Elsner et al, 2004a,b;Hanoch et al, 2006). Previous studies have demonstrated that iron sulfides make important contributions to the degradation of chlorinated solvents in natural systems (Devlin and Mü ller, 1999;Davis et al, 2003;Kenneke and Weber, 2003;Lookman et al, 2005;Darlington et al, 2008) as well as engineered systems (Kennedy et al, 2006a,b). These studies demonstrated the potential and important roles that iron sulfides could play in the degradation and natural attenuation of groundwater contaminants.…”
Section: Tce Degradation In the Presence Of Fesmentioning
confidence: 99%
See 1 more Smart Citation
“…1a. resulting in high enrichment of δ 13 C in cis-DCE. Combined biotic and abiotic transformation of TCE and cis-DCE was also found to proceed in an anaerobic microcosm experiment with sandstone (Darlington et al, 2008). Liang et al (2007) reported strong carbon isotope fractionation during abiotic degradation of PCE (enrichment factor of −30.2‰) and TCE (enrichment factor of −33.4‰) by FeS.…”
Section: Biotic and Abiotic Degradations Of Tce And 111-tca In The mentioning
confidence: 79%
“…Dhc containing the gene tceA have been found to respire TCE and cis-DCE (Seshadri et al, 2005) whereas Dhc with the genes vcrA or bvcA respire cis-DCE and vinyl chloride (VC) (Muller et al, 2004;Sung et al, 2006). Several recent laboratory studies have also suggested that abiotic degradation pathways for chlorinated ethenes are of importance in the presence of iron minerals (Darlington et al, 2008;Ferrey et al, 2004;He et al, 2008He et al, , 2010Jeong et al, 2011;Lollar et al, 2010). Biotic and abiotic degradations of chlorinated ethenes and ethanes have been documented by compound specific isotope analysis (CSIA) in several studies (for chlorinated ethenes e.g.…”
Section: Introductionmentioning
confidence: 99%